Comparison of open surgery versus endoscopic-assisted release for gluteal muscle contracture: a systematic review and meta-analysis - YaMeng Jiang; Tao Li; Li Wang; Gang Chen; Jian Li (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Purpose This study aimed to perform a systematic review and meta-analysis to compare the clinical outcomes of open surgery and arthroscopic release in gluteal muscle contracture (GMC). Methods Two independent reviewers YM and WL conducted a systematic search of PubMed, Embase, Cochrane Library, and Web of Science to identify clinical trials that adhered to the PRISMA guidelines (Appendix A), spanning from inception to July 2023. Search items included ((“gluteal” OR “gluteus”) AND (“contracture” OR “fibrosis”)). Research comparing open surgery or arthroscopic release was included. Clinical outcomes were compared using the risk ratio for dichotomous variables and the standardized mean difference for continuous variables. A P value < 0.05 was deemed statistically significant. Results Four studies with 453 patients met the selection criteria and were included in this review. Compared with open surgery, in the case of similar postoperative functional satisfaction (1.21, 95% CI = 0.46–3.17, P = 0.70), the arthroscopic release achieved advantages in postoperative complications (3.5, 95% CI = 1.75–7.03, P = 0.0004), cosmetic satisfaction (0.07, 95% CI = 0.01–0.65, P = 0.02), length size (5.65, 95% CI = 4.11–7.19, P < 0.001), and hospitalization duration (1.57, 95% CI = 0.89 to 2.26, P < 0.001). Conclusion This research shows that both open surgery and arthroscopic release improve functional satisfaction. The arthroscopic release could result in fewer complications, better cosmetic satisfaction, shorter length size, and shorter hospitalization duration. Registration and protocol There is no registration and protocol for this meta-analysis.